2009
DOI: 10.1634/theoncologist.2008-0213
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Benefit of Bevacizumab in Metastatic Colorectal Cancer Is Independent of K-ras Mutation Status: Analysis of a Phase III Study of Bevacizumab with Chemotherapy in Previously Untreated Metastatic Colorectal Cancer

Abstract: The content of this article has been reviewed by independent peer reviewers to ensure that it is balanced, objective, and free from commercial bias. No financial relationships relevant to the content of this article have been disclosed by independent peer reviewers. ABSTRACTPurpose. Mutations of the K-ras gene were identified as a prognostic marker in metastatic colorectal cancer (mCRC). In addition, emerging data suggest that K-ras mutations are a negative predictor of clinical benefit from anti-epidermal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(166 citation statements)
references
References 18 publications
14
147
0
5
Order By: Relevance
“…In KRAS exon 2 mutant patients BEV addition to IFL compared to IFL significantly increased PFS up to 9.3 months, while not OS and activity [4,30]. KRAS exon 2 status, wildtype or mutant, does not significantly affect clinical outcome of MCRC patients treated with BEV-containing chemotherapy.…”
Section: C35 G > a Kras Mutation In Mcrc Patients: Prognostic Relevamentioning
confidence: 85%
See 3 more Smart Citations
“…In KRAS exon 2 mutant patients BEV addition to IFL compared to IFL significantly increased PFS up to 9.3 months, while not OS and activity [4,30]. KRAS exon 2 status, wildtype or mutant, does not significantly affect clinical outcome of MCRC patients treated with BEV-containing chemotherapy.…”
Section: C35 G > a Kras Mutation In Mcrc Patients: Prognostic Relevamentioning
confidence: 85%
“…Retrospective analysis showed that KRAS exon 2 mutant status did not significantly affect median OS (19.9 and 27.7 months, in KRAS mutant and wild-type patients, respectively) of MCRC patients treated with BEV added to IFL [29,30]. Prognostic relevance of KRAS exon 2 or BRAF mutant genotype was not significantly different compared to KRAS or BRAF wild-type status.…”
Section: Ras Genotype In Metastatic Colorectal Cancer (Mcrc) Patientsmentioning
confidence: 92%
See 2 more Smart Citations
“…Hurwitz et al (2004) demonstrated that bevacizumab significantly improved OS in mCRC patients, with median OS (mOS) of 20.3 months in patients receiving irinotecan, bolus fluorouracil, and leucovorin (IFL) plus bevacizumab, relative to 15.6 months in patients who received IFL alone. They also retrospectively analyzed plasma and tumor VEGF levels and KRAS mutational status but found no association between these biomakers and survival benefits from bevacizumab (Hurwitz et al, 2009). Scartozzi et al (2009) suggested a possible correlation between bevacizumab-induced hypertension and clinical outcomes in CRC patients treated with first-line bevacizumab.…”
Section: Molecular Markers Of Vegf Inhibitormentioning
confidence: 99%